Anchoring Science and Technology in Greco-Roman Antiquity - Flohr, Miko; Mols, Stephan; Tieleman, Teun (Classical Studies E-Books Online, Collection 2024., 2025)
This collection of essays explores processes of innovation in Greco-Roman technology and science. It uses the concept of 'anchoring' to investigate the microhistories of technological and scientific practices and ideas. The volume combines broad, theoretical essays with more targeted case studies of individual inventions and innovations. In doing so, it moves beyond the emphasis on achievement that has traditionally characterized modern scholarship on ancient technology and science. Instead, the chapters of this volume analyse the manifold ways in which new technologies and ideas were anchored in what was already known and familiar, and highlight how, once familiar, technologies and ideas could themselves become anchoring points for inventions and innovations.